Chiral N-Heterocyclic Carbene−Pd(0)-Catalyzed Asymmetric Diamination of Conjugated Dienes and Triene - Xu, Liang; Shi, Yian (Journal of organic chemistry, 2008)
Studies show that a variety of conjugated dienes and triene can be enantioselectively diaminated using di-tert-butyldiaziridinone as nitrogen source and chiral N-heterocyclic carbene−Pd(0) complex as catalyst in good enantioselectivity (62−91% ee) with high regio- and diastereoselectivity.